Post-harvest handling of coffee and making liquid organic fertilizer for environmental sustainability Harjokuncaran Village - Nabilah Azhar Khoirunnisa; Afifa Husna; Elfi Anis Saati (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang)
Harjokuncaran Village possesses significant potential for Robusta coffee (Coffea canephora) cultivation; however, the quality of the coffee remains suboptimal, and prolonged use of chemical fertilizers has led to soil degradation. To address these challenges, a community service program was implemented focusing on farmer education in post- harvest handling, encompassing harvesting, sorting, drying, and storage, as well as the production of liquid organic fertilizer (LOF). The program aimed to enhance the knowledge and practical skills of local coffee farmers while promoting the adoption of environmentally friendly agricultural practices using LOF derived from livestock waste, rice washing water, coconut water, and rice bran. The program involved surveys, observations, and hands-on workshops attended by 25 coffee farmers. Pre- and post-tests were conducted to evaluate the program's effectiveness and support long-term implementation. During the workshops, participants actively engaged in discussions and practiced both post-harvest techniques and LOF production. Results demonstrated a significant increase in farmers’ understanding, with knowledge levels improving from 8–92 percent to 92–100 percent. Additionally, the adoption of proper red cherry picking and improved post-harvest practices led to noticeable enhancements in coffee quality. Farmers’ awareness and ability to produce and use LOF also rose sharply from 4 percent to 100 percent. This program effectively strengthened farmers' competencies in sustainable coffee farming and fostered collaboration between the implementation team and local stakeholders to support continued agricultural and environmental development in the village.